Early technical pancreas failure in Simultaneous Pancreas–Kidney Recipients does not impact renal allograft outcomes. Issue 1 (20th November 2020) - Das, Devika M.; Huskey, Janna L.; Harbell, Jack W.; Heilman, Raymond L.; Singer, Andrew L.; Mathur, Amit; Neville, Matthew R.; Morgan, Paige; Reddy, Kunam S.; Jadlowiec, Caroline C.
Abstract: Early pancreas loss in simultaneous pancreas–kidney (SPK) transplants has been associated with longer perioperative recovery and reduced kidney allograft function. We assessed the impact of early pancreas allograft failure on transplant outcomes in a contemporary cohort of SPK patients ( n = 218). Early pancreas allograft loss occurred in 12.8% ( n = 28) of recipients. Delayed graft function (DGF) was more common (21.4% vs. 7.4%, p = 0.03) in the early pancreas loss group, but there were no differences in hospital length of stay (median 6.5 vs. 7.0, p = 0.22), surgical wound complications ( p = 0.12), or rejection episodes occurring in the first year ( p = 0.87). Despite differences in DGF, both groups had excellent renal function at 1 year post‐transplant (eGFR 64.1 ± 20.8 vs. 65.8 ± 22.9, p = 0.75). There were no differences in patient (HR 0.58, 95% CI 0.18–1.87, p = 0.26) or kidney allograft survival (HR 0.84, 95% CI 0.23–3.06, p = 0.77). One‐ and 2‐year protocol kidney biopsies were comparable between the groups and showed minimal chronic changes; the early pancreas loss group showed more cv changes at 2 years ( p = 0.04). Current data demonstrate good outcomes and excellent kidney allograft function following early pancreas loss.